The Effect of Lactation Massage on Increasing Breast Milk Production in Breastfeeding Mothers at BPM Nurhidayah Tambusai District, Rokan Hulu - Rika Herawati; Andriana Andriana; Elvira Junita; Heny Sepduwiana; Herma Yesti; Masdi Janiarli; Andria Andria; Ermiza Ermiza; Primawaty Dwi Rijsubo; Romy Wahyuny; Siti Aroh (International Journal on Advanced Science, Education, and Religion, 2023)
Lactation massage for post partum mothers can be used as a non-pharmacological therapy to stimulate oxytocin to accelerate lactation turnover. If lactation occurs quickly, the baby must receive breast milk as the first nutrition. Examination of exclusive breastfeeding can help reduce the infant mortality rate which is still high in Indonesia. The low coverage of exclusive breastfeeding for babies under six months is partly caused by the hampered breast milk production of postpartum mothers in the first days after giving birth so that most babies receive formula milk. Efforts to help achieve the role of postpartum mothers include lactation massage intervention and the influence of lactation massage. The aim of this research is to find out the effect of lactation massage on breast milk production in breastfeeding mothers. This research is experimental research (two group pretest and posttest design) carried out between May-July 2024 with a purposive sampling research design. The population in this study was 30 postpartum mothers, with a sample of 30 postpartum mothers in BPM Nurhidayah, Tambusai District, with an experimental group of 15 people and a control group of 15 breastfeeding mothers. The results of the independent mean difference test T test show that the p value = 000 < 0.05, meaning there is a difference in the average increase in breast milk volume in the control group which was not given lactation massage, namely the experimental group with a mean value of 115.80 and the control group with The mean value is 73.33, meaning 115.80 > 73.33, so it can be concluded that there is an increase in breast milk production before and after lactation massage. It is hoped that postpartum mothers can understand and increase their knowledge and be able to apply it.